PULSE WAVE VELOCITY PROGRESSIONE OVER A 3.7 YEARS FOLLOW-UP: FOCUS ON METABOLIC SYNDROME. (June 2018) - Maloberti, A.; Vallerio, P.; D'Angelo, L.; Fachetti, R.; Occhi, L.; Panzeri, F.; Sirico, D.; Buono, A.; Giupponi, L.; Triglione, N.; Montero, B. Lopez; Casati, M.; et al.
Abstract : Objective: The role of classic cardiovascular risk factors on the progression of arterial stiffness has not yet been extensively evaluated particularly regarding Metabolic Syndrome (MS). The aim of the current longitudinal study was to evaluate the determinants of the Pulse Wave Velocity (PWV) progression over a 3.7 years follow-up period in hypertensive subjects focusing on metabolic syndrome. Design and method: We enrolled 448 consecutive hypertensive outpatients 18–80 aged, followed by the Hypertension Unit of St. Gerardo Hospital (Monza, Italy). At baseline anamnestic, Blood Pressure (BP) and laboratory data as well as cf-PWV were assessed. We performed PWV again at a follow-up examination with a median time amounting to 3.7 ± 0.5 years. NCPET-ATPIII criteria were used to define MS as the presence of three or more item. Data are reported as mean ± SE. Results: At T0 the mean age was 53.7 ± 1.1 years, SBP and DBP were 141.3 ± 1.7 and 86.4 ± 1.2 mmHg and PWV was 8.5 ± 0.15 m/s. 125 patients (27.9%) meet the criteria for MS. Those patients were older (56.3 ± 1.0 vs 52.7 ± 0.7, p = 0.007) with superimposable baseline SBP and DBP values (141.4 ± 1/87.2 ± 0.6 vs 142.4 ± 1.6/86 ± 1, p > 0.05 for both comparison) as well as PWV values (8.7 ± 0.18 vs 8.58 ± 0.1, p = 0.43). At follow-up examination MS subjects showed a lower decreas in SBP/DBP (SBP: −4.7 ± 1.7 vs −10.2 ± 1.1; DBP: −5.1 ± 1.1 vs −8.3 ± 0.7, p < 0.01 for both comparison) with a higher increase in PWV values (1.1 ± 0.2 vs 0.39 ± 0.1, p = 0.03). This difference remain significant also in a multivariate model with age, sex, smoking, baseline PWV and delta MBP as covariates. Conclusions: arterial aging and BP values in treated hypertensive subjects during a 3.7 years follow-up seems to be influenced by the presence of MS. In fact subjects with MS showed a worse BP control and an increase in PWV values during the follow-up. PWV changes over time would probably give important information that need further future research studies.